2019
DOI: 10.1021/acs.organomet.8b00936
|View full text |Cite
|
Sign up to set email alerts
|

Paddle Ball Dynamics during Conversion of a Rh–Methyl Hydride Complex to a Rh–Methane σ-Complex through Reductive Coupling

Abstract: We used quasiclassical direct dynamics simulations to examine reaction pathways for protonation-induced reductive coupling of a pincer (PONOP)­Rh–methyl hydride complex. These dynamics simulations revealed that the majority of trajectories (>90%) emerging from a vibrationally averaged velocity distribution of the Rh–methyl hydride reductive coupling transition state led to the Rh–methane σ-complex. Only a few trajectories (<10%) dynamically deviated and did not sample this σ-complex structure and resulted in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…We discuss this interaction in more detail in Section . In general, the calculated distances for the metal-methane interaction in 2 agree well with those of other σ-methane complexes. ,,,, In the final part of the reaction coordinate, the dissociation of methane from 2 produces the dissociated state 3 , in which the metal center and the methane molecule no longer interact.…”
Section: Resultssupporting
confidence: 72%
“…We discuss this interaction in more detail in Section . In general, the calculated distances for the metal-methane interaction in 2 agree well with those of other σ-methane complexes. ,,,, In the final part of the reaction coordinate, the dissociation of methane from 2 produces the dissociated state 3 , in which the metal center and the methane molecule no longer interact.…”
Section: Resultssupporting
confidence: 72%
“…Formation of this product occurred in less than 50 fs. Trajectories starting from TS 1 in the reverse (away from products) direction showed initial motion towards the singlet σ-coordination structure INT 2 but then quickly reverted to the forwards direction in a paddle ball type motion 43 and like the forward direction trajectories only resulted in formation of I (see ESI † ).…”
Section: Resultsmentioning
confidence: 97%
“…Consistent with experiment, quasiclassical trajectories started at the reductive coupling transition state showed that most trajectories (>90%) led to the Rh−methane σ-complex (Figure 9). 64 Less than 10% of trajectories did not sample this σ-complex structure and resulted in direct methane dissociation. This indicates that the σ-complex connected to the Rh-methyl hydride is not the result of methane rebounding back to the Rh metal center due to a solvent cage but is on the reactive trajectory pathway.…”
Section: One Step Two Steps or Something Inmentioning
confidence: 99%